1997
DOI: 10.1093/mnras/292.3.723
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary tracks of FRII sources through the P-D diagram

Abstract: This is the second in a series of papers presenting an analytical model for the evolution of FRII radio sources. In this paper we evaluate the expected radio emission from a radio source incorporating energy loss processes for the relativistic electrons. By combining these results with our earlier dynamical model we calculate evolutionary tracks through the Power-Linear size diagram. These tracks are in good agreement with the observed distribution of sources in this diagram. The effects of different forms for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
209
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(221 citation statements)
references
References 19 publications
11
209
1
Order By: Relevance
“…The clear deficiency of giants of high radio luminosity suggests that the luminosity of radio sources decreases as they evolve. The evolutionary tracks suggested by Kaiser et al (1997), which are shown in the figure, are roughly consistent with the data. However, in the models developed by Blundell, Rawlings & Willott (1999), the luminosity declines more rapidly than the Kaiser et al tracks, providing a somewhat better fit to the upper envelope for large linear sizes.…”
Section: Evolution Of Giant Radio Sourcessupporting
confidence: 83%
“…The clear deficiency of giants of high radio luminosity suggests that the luminosity of radio sources decreases as they evolve. The evolutionary tracks suggested by Kaiser et al (1997), which are shown in the figure, are roughly consistent with the data. However, in the models developed by Blundell, Rawlings & Willott (1999), the luminosity declines more rapidly than the Kaiser et al tracks, providing a somewhat better fit to the upper envelope for large linear sizes.…”
Section: Evolution Of Giant Radio Sourcessupporting
confidence: 83%
“…A negative radio power evolution is indeed expected for active radio radio sources (cf. Kaiser et al 1997;Blundell et al 1999). On the other hand, the observed effect can also be caused if a substantial fraction of the GRGs stop their radio activity (and "fade") before they reach a size of 3 Mpc.…”
Section: The 2-mpc Linear Size Cut-offmentioning
confidence: 99%
“…Kaiser et al 1997;Blundell et al 1999) predict the radio power and linear size evolution of powerful radio sources with time. According to these models, GRGs must be extremely old (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This appears large at first glance, but it becomes actually small with regard to the range of more than four decades of power. In view of the complexity of the objects, with a diversity of the strength of the thermal IR dust bump, evolving giant radio lobes (Kaiser et al 1997;Blundell & Rawlings 1999) and various circumgalactic environments (Barthel & Miley 1988), such a dispersion is certainly not surprising. Therefore, the striking similarity of the R dr distributions for quasars and galaxies provides strong evidence in favour of the basic role of the orientationdependent unification.…”
Section: Radio-infrared-comparisonmentioning
confidence: 99%